Evaluation of Occupational Safety Performance Using Key Performance Indicators in Manufacturing Industrial Construction - Prasetya, Dimas Ardi; Dellarosa, Luvy; Hidayat, Bayu Rahmat (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Occupational Health and Safety (OHS) in work environments is crucial for optimal productivity. Work accidents affect productivity because they can reduce working hours and decrease productivity. The problem faced by a company is the absence of a Key Performance Indicator that explicitly considers the safety aspect. This study aims to determine and calculate the key performance indicator safety of KPIs and implement a correlation between work accidents and productivity. Key Performance Indicator data processing Safety consists of leading indicators for potential future events and lagging indicators for past accident data using the Safe T-Score method to determine the effect of accident rates on work productivity. The Key Performance Indicator calculation results for safety showed good performance, with a total actual value of 94.74%. The results show that the Safe T Score is 2.68 in 2022 and -1.61 in 2023, indicating little change in the occupational health and safety program. The results show a positive relationship between occupational safety and productivity; the fewer the accidents, the higher the productivity.